Taking Sides with Pain – Lateralization aspects Related to Cerebral Processing of Dental Pain - Brügger, Mike; Ettlin, Dominik A.; Meier, Michael; Keller, Thierry; Luechinger, Roger; Barlow, Ashley; Palla, Sandro; Jäncke, Lutz; Lutz, Kai (Frontiers in Human Neuroscience, 2011)
The current fMRI study investigated cortical processing of electrically induced painful tooth stimulation of both maxillary canines and central incisors in 21 healthy, right handed volunteers. A constant current, 150% above tooth specific pain-perception thresholds was applied and corresponding online ratings of perceived pain intensity were recorded with a computerized visual analog scale during fMRI measurements. Lateralization of cortical activations was investigated by a region of interest analysis. A wide cortical network distributed over several areas, typically described as the pain or nociceptive matrix, was activated on a conservative significance level. Distinct lateralization patterns of analyzed structures allow functional classification of the dental pain processing system. Namely, certain parts are activated independent of the stimulation site, and hence are interpreted to reflect cognitive emotional aspects. Other parts represent somatotopic processing and therefore reflect discriminative perceptive analysis. Of particular interest is the observed amygdala activity depending on the stimulated tooth that might indicate a role in somatotopic encoding.